Is the Electronic Open Limit Order Book Inevitable? - GLOSTEN, LAWRENCE R. (Journal of Finance, 1994)
ABSTRACT Under fairly general conditions, the article derives the equilibrium price schedule determined by the bids and offers in an open limit order book. The analysis shows: (1) the order book has a small‐trade positive bid‐ask spread, and limit orders profit from small trades; (2) the electronic exchange provides as much liquidity as possible in extreme situations; (3) the limit order book does not invite competition from third market dealers, while other trading institutions do; (4) If an entering exchange earns nonnegative trading profits, the consolidated price schedule matches the limit order book price schedule.